Design of an Array of a 2×1 Microstrip Antenna in the Wimax Band, 3.5 Ghz - Kaschel-Carcamo, H (Institute of Electrical and Electronics Engineers Inc., 2021)
This work describes an array of a 2×1 microstrip patch antenna with 3.5 GHz of center frequency for the WiMax applications. In order to design and simulate this array of two by one with microstrip line feed technique, the software used was the Computer Simulation Tool (CST) by Microwave. The design of the antenna array was made on Rogers RO3035 substrate with the following characteristics: overall size of 110 × 87× 1.52mm3 and dielectric substrate with σr=3.5. The structural design for the antenna was created on the CST software and the characteristic impedance for the transmission line model was used as the basis. The following are the characteristics of the microstrip antenna: small size, light weight, low cost, compatibility with rigid surfaces. Microstrip antennas are low-profile antennas. At first, a single-patch microstrip antenna was designed and simulated, obtaining results that are represented in graphics. Next, a 2×1 square patch microbrand antenna array was designed. © 2021 IEEE.